Pengaruh Persaingan Dan Kekuatan Pembeli Terhadap Hubungan Pemasok-Ritel Modern Di Jakarta - Martadisastra, Dedie S. (Jurnal Manajemen, 2014)
The Ã‚Â aim Ã‚Â of the Ã‚Â study was to investigate theÃ‚Â  development Ã‚Â of domestic supplier Ã‚Â perfrmances Ã‚Â as the Ã‚Â result of modem Ã‚Â retail-supplier Ã‚Â businessÃ‚Â  relationships which they Ã‚Â had Ã‚Â controlled Ã‚Â by theÃ‚Â  effect of combinations Ã‚Â on competition and buyer power. Ã‚Â The Ã‚Â paper Ã‚Â presents Ã‚Â the Ã‚Â results Ã‚Â of a Ã‚Â surveyÃ‚Â  of packaged Ã‚Â processed Ã‚Â foods suppliers, Ã‚Â which Ã‚Â formed Ã‚Â part Ã‚Â of a Ã‚Â wider Ã‚Â study Ã‚Â ofÃ‚Â  buyer-supplier Ã‚Â relationships Ã‚Â in Indonesia's modem Ã‚Â retail supply chains. The findings of this study indicate that the results demonstrate the heterogeneity relationships between supplier and modem retail in the main commodity grocery sectors. The extent to which modem retail challenged by competition, Ã‚Â supply chain strategy and market share are likely to influence the way in Ã‚Â which modem retail deal with suppliers. Ã‚Â A part of the suppliers indicated that they get benefited Ã‚Â substantially from the presence of modem retail, Ã‚Â however, they also face several Ã‚Â challenges Ã‚Â broughtÃ‚Â Ã‚Â  Ã‚Â aboutÃ‚Â  by buyer Ã‚Â power as Ã‚Â imposition Ã‚Â of several Ã‚Â unfair relationship terms, price fixing, and poorly supervision as cause of the development and growth of suppliers limitedly. This study attempts to show the results of the research in Indonesia to empirically measure the effect of competition and buyer power on modem retail-supplier relationships. The further research is needed to refine the results of this initial study.Ã‚Â